Evaluation of Edible Film and Capsule Shell Characteristics Based on Catfish Skin Gelatin (Pangasius hypophthalmus) Incorporated with Konjac Glucomannan - Azlaini Yus Nasution; Ramayani; Deri Islami (Jurnal Ilmu Kesehatan Abdurrab, 2026)
Gelatin is a raw material used in the manufacture of capsule shells and is obtained through the partial hydrolysis of collagen derived from animal skin or bones. Catfish (Pangasius hypophthalmus) skin is considered an alternative source of halal and sustainable gelatin. The addition of konjac glucomannan (KGM), a natural polysaccharide extracted from konjac tubers and composed of glucose and mannose units, is expected to improve the physical characteristics of the resulting capsule shells. This study aimed to evaluate the characteristics of edible films and capsule shells based on catfish skin gelatin with the addition of konjac glucomannan at concentrations of 6%, 7%, and 8%. The characterization of the edible films included pH, thickness, tensile strength, and elongation percentage. The capsule shells were evaluated based on shell dimensions, shell volume, moisture content, and disintegration time in water and acidic medium. The results showed that all formulations met the specified requirements for pH, thickness, tensile strength, elongation percentage, capsule shell volume, and disintegration time in water. Based on these findings, it can be concluded that catfish skin gelatin supplemented with konjac glucomannan has the potential to be used as a raw material for hard capsule shells. However, further formulation optimization is required to improve product quality, particularly with respect to moisture content and disintegration time in acidic medium.